Analysis on the cognitive impact of social mobile games on left-behind children in the era of big data - Mengyu, Li; Jinglei, Li; Yasin, Megat Al Imran; Osman, Mohd Nizam; Hashim, Norliana; Lay, Hoon Ang; Yitian, Xue (Frontiers Media, 2022)
The popularity of mobile gaming has become a common sight in rural areas, and the problem of left-behind children's mobile gaming has become the biggest challenge faced by rural education, and has become a hot topic in the education sector and society. The stage of left-behind children is the golden period of learning and growth. However, this stage is also the period when they have the greatest fluctuations in their ideology due to various factors such as guardians and youths. With the development of big data, it has been applied to various aspects of people's life. This article is mainly based on qualitative research, with the interview and observation as the main methods, supplemented by a questionnaire survey method. In the empirical analysis part, this article has a certain degree of expansion in data selection and research methods. Compared with previous studies, we increased the scale of the research data, making the research results more meaningful. In the research method, the ordinary least squares method (OLS), the propensity score matching method (PSM) and the two-stage least square method (2SLS) are used, and multiple control variables are selected. The factor analysis of the original scores of the historical knowledge test and the original scores of the two-dimensional cultural value evaluation are carried out to obtain the factor scores of cognitive ability. The emotion of the child is expressed by the depression score, and factor analysis is also performed on the depression score. Cognitive abilities refer to reasoning or thinking, processing speeds, and one's ability to solve problems in novel situations, independent of acquired knowledge. OLS regression results show that left-behind children are inferior to non-left-behind ones in cognitive ability. Moreover, left-behind children are more likely to be emotionally depressed. And whether the children are accompanied by migrant or rural parents, there is no significant difference in their cognitive ability and emotions. Because there are unobservable factors that affect whether children are left-behind and children's cognitive abilities and emotions, the sample may have a self-selection bias. This research focuses on the phenomenon of left-behind children's mobile gaming, revealing the compromised cognitive abilities of these marginalized children groups. Our study might put a wake-up for authorities on the education in rural areas.